Angklung Buhun: Peran dalam Ritus Pertanian Masyarakat Kasepuhan Adat Gelaralam - Dani Yanuar; Ullum Fadilla Fauzan (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
Angklung buhun is an art form whose involvement is very dominant in various traditional ritual contexts, especially in agricultural ritual activities. Angklung buhun is played as a ritual tool starting from the process of opening agricultural land, planting rice seeds, maintenance, to harvesting. This research explains the role of angklung buhun in the agricultural rites of the Kasepuhan Adat Gelaralam community. The research method used is a qualitative method with an ethonographic approach to understand a view of life from the perspective of the culture owner with the stages of selecting informants, conducting interviews, analyzing data and data processing. The results of this research reveal that the existence of angklung buhun is one of the essential art forms and has a deep meaning for the Kasepuhan Gelaralam community. This is proven when angklung buhun cannot be played carelessly, this shows that angklung buhun becomes a spiritual and ritual medium. In the context of agricultural rites, angklung buhun functions as a medium for delivering prayers in the ngaseuk, mabay, mipit, ngadiukeun, nganyaran, and serentaun rituals. Angklung buhun is not just seen as a sound medium that creates the impression of a meaningless crowd. Furthermore, angklung buhun is an object that stores positive energy that is believed to have an impact in strengthening harmonious relationships between society, nature, and the almighty creator. These beliefs are closely related to the way the people view nature, ancestors and spirituality.